High prevalence of vitamin D insufficiency in community-dwelling postmenopausal Polish women - Stolarczyk, Artur; Horvath, Andrea; Szczechura, Monika; Kamińska, Magda; Dziechciarz, Piotr (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction: Inadequate vitamin D level is associated with altered bone turnover and bone loss, which increases the fracture risk. Aim: To assess the seasonal prevalence of inadequate (insufficient or deficient) serum vitamin D levels in community-dwelling postmenopausal Polish women screened for osteoporosis. Material and methods : A cross-sectional observational study based on the regional urban non-institutionalized sample (n = 107) of postmenopausal Caucasian women in the age range of 51-83 years, not taking any medication and free from any condition likely to affect vitamin D status or calcium/bone metabolism. The outcome measures were the mean 25-OH vitamin D level across all the seasons and the percentage of vitamin D deficiency and insufficiency and defined as < 20 ng/dl (50 nmol/l) and 20-30 ng/dl (50-75 nmol/l), respectively. Results: No statistically significant difference has been found in the mean vitamin D level, regardless of the season (p = 0.4). The prevalence of vitamin D deficiency and insufficiency were in spring 54% and 32%, in summer 46% and 46%, in autumn 67% and 27%, and in winter 61% and 22%, respectively. Conclusions : Vitamin D inadequacy is common in a sample of Polish community-dwelling postmenopausal women regardless of the season.